Dhofar through the ages : an ecological, archaeological and historical landscape - Newton, Lynne S., (Archaeological heritage of Oman ;, 2019)
Dhofar, the southern governorate of Oman, lies within a distinctive ecological zone due to the summer Southwest Monsoon. Archaeological surveys and excavations in the governorate, beginning in 1954, have brought to light Dhofar's ancient past stretching back to the Lower Paleolithic ca. 1.5 my BP.